2014
DOI: 10.3389/fpsyg.2013.01018
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral evidence of a dissociation between voice gender categorization and phoneme categorization using auditory morphed stimuli

Abstract: Both voice gender perception and speech perception rely on neuronal populations located in the peri-sylvian areas. However, whilst functional imaging studies suggest a left vs. right hemisphere and anterior vs. posterior dissociation between voice and speech categorization, psycholinguistic studies on talker variability suggest that these two processes share common mechanisms. In this study, we investigated the categorical perception of voice gender (male vs. female) and phonemes (/pa/ vs. /ta/) using the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Analyses of perceptual distances (d') between successive pairs of items along continua revealed that none of the patient groups had increased perceptual distances for ambiguous items (figure 3), contrary to healthy subjects as shown in (Pernet et al, 2014). This result indicates a generalized reduction in categorical boundaries following stroke.…”
Section: Behavioral Quantitative Analysesmentioning
confidence: 87%
See 4 more Smart Citations
“…Analyses of perceptual distances (d') between successive pairs of items along continua revealed that none of the patient groups had increased perceptual distances for ambiguous items (figure 3), contrary to healthy subjects as shown in (Pernet et al, 2014). This result indicates a generalized reduction in categorical boundaries following stroke.…”
Section: Behavioral Quantitative Analysesmentioning
confidence: 87%
“…Paradigm: The experiment was identical to (Pernet et al, 2014), except that only pitch equalized stimuli were used. Participants carried out with two 2 alternative forced choice identification tasks: voice gender (male vs. female) and phoneme (/pa/ vs. /ta/), and responded by button press on a keyboard.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations